2021
DOI: 10.46234/ccdcw2021.249
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in the Epidemiology of HIV/AIDS in China

Abstract: After thirty-two years since the first domestic outbreak of human immunodeficiency virus (HIV)/ acquired immune deficiency syndrome (AIDS) among injection drug users (IDUs) and almost two decades of comprehensive response efforts by the Chinese government, HIV/AIDS remains a major public health problem. The increasing burden of HIV/AIDS and comorbidities, the emergence of new HIV subtypes and/or circulating recombinant forms and drug mutations, the changing transmission networks, and the urgency of immediate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 56 publications
(111 reference statements)
0
59
1
1
Order By: Relevance
“…The median number of PEP prescriptions recorded per day was 8 (4-15) during the 1,117 days before NPIs (23 January, 2020), compared with 4 (2-7) during the 76 days of NPIs (23 January, 2020 to 7 April, 2020, the NPIs period), and 14 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) during the 268 days post-NPIs (8 April, 2020 to 31 December, 2020, post-NPIs period). Poisson segmented regression analysis showed that the number of PEP prescriptions decreased by 71¢ 5% in the first week of the NPIs period (20-26 January, 2020) (incidence rate ratio [IRR] 0¢285; 95% confidence interval [CI] 0¢192-0¢423; Table 2 and Figure 2A; compared with counterfactual), then 71¢2% (0¢288, 0¢197-0¢ 423) and 70¢8% (0¢292, 0¢201-0¢424) in the second (27 January-2 February, 2020) and third week (3-9 February, 2020), respectively; the number of prescriptions showed an increasing trend of 2¢4% per week in the post-NPIs period (1¢024,1¢012-1¢037), and by the end of 2020 (28-31 December, 2020) the number of prescriptions still had not reached expected level (0¢523,0¢394-0¢696).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median number of PEP prescriptions recorded per day was 8 (4-15) during the 1,117 days before NPIs (23 January, 2020), compared with 4 (2-7) during the 76 days of NPIs (23 January, 2020 to 7 April, 2020, the NPIs period), and 14 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) during the 268 days post-NPIs (8 April, 2020 to 31 December, 2020, post-NPIs period). Poisson segmented regression analysis showed that the number of PEP prescriptions decreased by 71¢ 5% in the first week of the NPIs period (20-26 January, 2020) (incidence rate ratio [IRR] 0¢285; 95% confidence interval [CI] 0¢192-0¢423; Table 2 and Figure 2A; compared with counterfactual), then 71¢2% (0¢288, 0¢197-0¢ 423) and 70¢8% (0¢292, 0¢201-0¢424) in the second (27 January-2 February, 2020) and third week (3-9 February, 2020), respectively; the number of prescriptions showed an increasing trend of 2¢4% per week in the post-NPIs period (1¢024,1¢012-1¢037), and by the end of 2020 (28-31 December, 2020) the number of prescriptions still had not reached expected level (0¢523,0¢394-0¢696).…”
Section: Resultsmentioning
confidence: 99%
“…Data for all indicators except median time intervals and ART initiation showed a long-term increasing trend until 2020, which may be related to the rigorous efforts in massive HIV screening and testing strategies such as rapid expansion of voluntary counseling and testing clinics scale in the past decade. 17 The decrease in median time intervals may be due to the implementation of the “treat-all” in China starting in June 2016, while the steady trend in ART initiation may be due to a lack of momentum in the effects of this revision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, around 37.7 million people were living with HIV/AIDS globally, of which China had about 1.053 million people, and 351,000 cumulative reported deaths (1,2). Despite China has carried out a series of interventions (2), the HIV/AIDS epidemic has had a detrimental effect on people living with HIV/AIDS and their family members, including children and youths. Youths (aged [20][21][22][23][24][25][26][27][28][29][30] affected by parental HIV/AIDS, including youths who lost one or both of their parents to HIV/AIDS ("AIDS orphans") and youths who are living with HIV-infected parents ("Vulnerable children") (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…HIV/AIDS has been identified as a serious global public health concern. In 2020, around 37.7 million people were living with HIV/AIDS globally, of which China had about 1.053 million people, and 351,000 cumulative reported deaths ( 1 , 2 ). Despite China has carried out a series of interventions ( 2 ), the HIV/AIDS epidemic has had a detrimental effect on people living with HIV/AIDS and their family members, including children and youths.…”
Section: Introductionmentioning
confidence: 99%